"I am a radioactive mutant": Emergent biological subjectivities at Kazakhstan's Semipalatinsk Nuclear Test Site. (February 2016) - STAWKOWSKI, MAGDALENA E.
ABSTRACT: The Semipalatinsk Nuclear Test Site in Kazakhstan was conceived as an experimental landscape where science, technology, Soviet Cold War militarism, and human biology intersected. As of 2015, thousands of people continue to live in rural communities in the immediate vicinity of this polluted landscape. Lacking good economic options, many of them claim to be "mutants" adapted to radiation, while outsiders see them as genetically tainted. In such a setting, how do post‐Soviet social, political, and economic transformations operate with radioactivity to co‐constitute a "mutant" subjectivity? Today, villagers think of themselves as biologically transformed but not disabled, showing that there is no uniform way of understanding the effects of radioactive pollution, including among scientists. [ Kazakhstan, Semipalatinsk Nuclear Test Site, subjectivity, toxic environments, low‐dose radiation, nuclear testing ]